2014
DOI: 10.1120/jacmp.v15i2.4484
|View full text |Cite
|
Sign up to set email alerts
|

On using the dosimetric leaf gap to model the rounded leaf ends in VMAT/RapidArc plans

Abstract: Partial transmission through rounded leaf ends of Varian multileaf collimators (MLC) is accounted for with a parameter called the dosimetric leaf gap (DLG). Verification of the value of the DLG is needed when the dose delivery is accompanied by gantry rotation in VMAT plans. We compared the doses measured with GAFCHROMIC film and an ionization chamber to treatment planning system (TPS) calculations to identify the optimum values of the DLG in clinical plans of the whole brain with metastases transferred to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 26 publications
4
60
0
Order By: Relevance
“…The difference between the measured and optimized DLG values is caused by different contributions to the dose from the beam penumbra, which is a consequence of different patterns of leaf movement. Szpala et al (44) found out that the DLG values are a function of the distance (in the BEV) between the dose point and the leaf ending, and the width of the MLC slit. Therefore, calculation using a single DLG value may overestimate the measurement in the proximal penumbra, while it may underestimate the dose in the distal penumbra for RapidArc delivery (44) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the measured and optimized DLG values is caused by different contributions to the dose from the beam penumbra, which is a consequence of different patterns of leaf movement. Szpala et al (44) found out that the DLG values are a function of the distance (in the BEV) between the dose point and the leaf ending, and the width of the MLC slit. Therefore, calculation using a single DLG value may overestimate the measurement in the proximal penumbra, while it may underestimate the dose in the distal penumbra for RapidArc delivery (44) .…”
Section: Discussionmentioning
confidence: 99%
“…Szpala et al (44) found out that the DLG values are a function of the distance (in the BEV) between the dose point and the leaf ending, and the width of the MLC slit. Therefore, calculation using a single DLG value may overestimate the measurement in the proximal penumbra, while it may underestimate the dose in the distal penumbra for RapidArc delivery (44) . For IMRT delivery, the DLG values for smaller and larger regions average out and a single value can serve as the optimal value for different widths of the MLC slits (44) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4,12,24,27–38) Many of these publications are particularly applicable for use with Varian linear accelerators that use the Eclipse TPS. In this case, the dose contribution is adjusted by modifying the DLG that is adjusted during linac commissioning to account for differences in the radiation versus light projected field 33 , 36 . Others have developed methods for calibrating and commissioning the rounded leaf ends of the MLCs with the Pinnacle TPS for Elekta linacs with asymmetric jaws, 5 , 34 , 39 , 40 but they do not specifically address leaf gap doses that are not blocked by jaws as in the case for the Elekta beam modulator.…”
Section: Discussionmentioning
confidence: 99%
“…Rounded end MLCs suffer from bigger transmission penumbra and higher leaf-end radiation transmission. 9 For the current standard prescription dose to the target, 3DCRT plans usually meet the clinical standards. However, optimal jaw position can help reduce dose to OARs surrounding the target.…”
Section: Introductionmentioning
confidence: 99%